ANALYSIS OF REINFORCED CONCRETE DEGRADATION RISK BASED ON RAINFALL VARIABILITY AND EXTREME EVENTS IN THE COASTAL AREA OF PADANG CITY - Fadhil Sandy Pratama; Adrian Fadhli; Robby Hotter (Ikatan Dosen Menulis, 2025)
ainfall variability and extreme precipitation are critical environmental factors affecting the durability of reinforced concrete in coastal areas. This study aims to analyze the risk of reinforced concrete degradation in Padang City based on climate data from 2014 to 2024. The analysis was conducted by calculating mean monthly rainfall, standard deviation, coefficient of variation, and extreme thresholds (P90) to identify critical months with high wet exposure. Subsequently, concrete environmental classification according to SNI 2847:2019 was used to assess design implications on concrete quality and cover thickness. The results indicate that most months exhibit a coefficient of variation above 40%, with September–November identified as the most critical period for degradation risk. Extreme monthly rainfall during this period ranges from 589 to 769 mm, increasing wetting duration and wet–dry cycles, which may accelerate water penetration, carbonation, and reinforcement corrosion. These findings highlight the need for a durability-based design approach that adapts to local climatic conditions, particularly in specifying minimum concrete strength and cover thickness. This study provides a conceptual framework for evaluating reinforced concrete degradation risks in tropical coastal areas and offers guidance for designing more durable and sustainable structures.